PENGARUH PEMBERIAN BOKASHI DAUN GAMAL TERHADAP SERAPAN NITROGEN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays saccarata) PADA ENTISOL SIDERA - Safria Safria; Imam Wahyudi; Ramlan Ali (Universitas Tadulako, 2017)
The study aimed to determine the effect of gamal leafBokashiapplied toEntisolSidera on nitrogen uptake and yields of sweet corn. This research was conducted in February to June 2016 and located in Bulu Pountu Jaya village, Biromaru sub district, Sigi district, Central Sulawesi Province. This study used a randomized completelyblock design with seventreatments of bokashi rates i.e. control (g0), 10 ton/ha (g1), 15 ton/ha (g2), 20 ton/ha (g3), 25 ton/ha (g4), 30 ton/ha (g5), and 35 ton/ha (g6). Each treatment was replicated three times so that there were 21 experimental units. There is a significant effect on soil pH, soil organic, total soil N, plant N, Plant dry weight, N uptake and yield of sweet corn crop production.The research results showed that addingBokashi at therate of 35 ton/ha resulted in highes soil pH, total soil C-organic, total soil N, plant N, plant dry weight, N uptake and yields of sweet corn.